Kandungan Zat Gizi dan Potensi Antibakteri Ikan Laut Dalam di Selatan Jawa - Sugeng Heri Suseno; Ali Suman; Fanni Al Fanany (Universitas Gadjah Mada, 2006)
The research was mainly carried out to know nutrition composition and antibacterial potency of deep sea fish in south Java sea. Results showed that protein, fat, ash, and moisture contents of deep sea fish, Coelorincus longissimus, Coryphaenoides sp., Pereichthydae, Ophidiidae sp., Nomeidae, Satyrrichtys welchi, Dropus pragillis, Parascolopsis sp., Glytophidian sp., Hydrolagus sp., Ophidiidae, and one of unidentified species were 11.13-18.21%, 1.03-7.72%, 0.67-3.93%, and 70.70-86.30%, respectively. Nomeidae, S. welchi,. Parascolopsis sp., Hydrolagus sp., Ophidiidae, Pereichthydae, and one of unidentified species contained 17 amino acids with 9 essensial and 8 nonessensial amino acids. The essensial amino acids included histidine, arginine, threonine, valine, methionine, isoleucine, leucine, phenylalanine and lysine. The nonessensial amino acid were aspartic acid, glutamic acid, serine, glycine, alanine, proline, tyrosine, dan cysteine. Antibacterial experiment showed that meat extracts of Nomeidae, S. welchii, Parascolopsis sp. exhibited antibacterial activity against Staphylococcus aureus at 700 ppm with 0.25-2 mm of inhibitor zones. Meat extract of Nomeidae, S. welchii, Parascolopsis sp., Hydrolagus sp. at the same concentra-tion also produced 0.5-5 mm inhibition zones against Eschericia coli. Meat extract of S. welchii at 1,000 ppm produced 36 and 30 mm inhibition zones against S. aureus and E. coli, respectively.